Expression patterns of tight junction proteins in porcine major salivary glands: a comparison study with human and murine glands. Issue 2 (31st May 2018) - Zhang, Xue‐Ming; Huang, Yan; Zhang, Kuo; Qu, Ling‐Han; Cong, Xin; Su, Jia‐Zeng; Wu, Li‐Ling; Yu, Guang‐Yan; Zhang, Yan
Abstract: Tight junction (TJ) proteins play a dynamic role in paracellular fluid transport in salivary gland epithelia. Most TJ studies are carried out in mice and rats. However, the morphology of rodent salivary glands differs from that of human glands. This study aimed to compare the histological features and the expression pattern of TJ proteins in porcine salivary glands with those of human and mouse. The results showed that porcine parotid glands were pure serous glands. Submandibular glands (SMGs) were serous acinar cell‐predominated mixed glands, whereas sublingual glands were mucous acinar cell‐predominated. Human SMGs were mixed glands containing fewer mucous cells than porcine SMGs, whereas the acinar cells of murine SMGs are seromucous. The histological features of the duct system in the porcine and human SMGs were similar and included intercalated, striated and excretory ducts, but the murine SMG contained a specific structure, the granular convoluted tubule. TJ proteins, including claudin‐1 to claudin‐12, occludin and zonula occludin‐1 (ZO‐1), were detected in the porcine major salivary glands and human SMGs by RT‐PCR; however, claudin‐6, claudin‐9 and claudin‐11 were not detected in the murine SMG. As shown by immunofluorescence, claudin‐1, claudin‐3, claudin‐4, occludin and ZO‐1 were distributed in both acinar and ductal cells in the porcine and human SMGs, whereas claudin‐1 and claudin‐3 were mainly present in acinar cells, and claudin‐4 was mainly distributed in ductal cells in the murine SMG. In addition, 3D images showed that the TJ proteins arranged in a honeycomb‐like structure on the luminal surface of the ducts, whereas their arrangements in acini were irregular in porcine SMGs. In summary, the expression pattern of TJ proteins in salivary glands is similar between human and miniature pig, which may be a candidate animal for studies on salivary gland TJ function.